Queera lustar: Fan fiction i vampyrmiljö - Isaksson, Malin; Lindgren Leavenworth, Maria (Tidskrift för litteraturvetenskap, 2009)
Queer Desires: Fan Fiction about Vampires and Slayers In this article we analyze a selection of fan fiction stories in which fans engage in an intertextual dialogue with a source text. As an Internet-published literary form, fan fiction (or fanfic) is fairly new and the relatively democratic means of publication have meant a dramatically increased production. However, the intertextual dialogue with the source text reveals connections between fanfic and previous forms of rewritings. It is therefore rather in terms of content that fan fiction can be said to represent new strategies when negotiating the source material. The six fanfics chosen for the analyses are of the slash and femslash varieties in which samesex couples who are not romantically or sexually linked in the source text are paired. The fanfics take as their starting points Joss Whedon’s tv-series Buffy the Vampire Slayer and J. R. Ward’s romantic novels in the Black Dagger Brotherhood series. Authors of femslash pair the two Slayers Buffy and Faith and authors of slash engage the characters Vishous and Butch in a homoerotic relationship. Aside from analyzing examples of the fanfic form, the selection of stories based on source texts centering on vampires means an opportunity to investigate the function of this literary trope. Its attraction for fanfic authors can be said to stem from the figure’s inherent possibilities of representing alternative, queer sexualities. By analyzing narrative strategies and selected themes we argue that the (fem)slash texts illustrate negotiations both with genre and gender conventions of the source texts and a resistance to the heteronormative structures of today’s popular culture.